2021
DOI: 10.1177/03000605211044366
|View full text |Cite
|
Sign up to set email alerts
|

Identification of independent risk factors for diabetic neuropathy progression in patients with type 2 diabetes mellitus

Abstract: Objective To identify independent risk factors for diabetic neuropathy (DN) in patients with type 2 diabetes mellitus (T2DM). Methods We retrospectively analyzed 376 patients with T2DM at the First Affiliated Hospital of Fujian Medical University, China between January 2013 and October 2016. Multivariate logistic regression was used to explore potential risk factors for progression of DN in patients with T2DM. Effect sizes were estimated using odds ratios (ORs) and 95% confidence intervals (CIs). Results The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
4
2
0
Order By: Relevance
“…In line with our findings, Huang et al. ( 40 ) reported that the use of insulin is an independent risk factor for DPN in patients with type 2 diabetes. On the other hand, metformin possibly attenuated neuropathic pain in a diabetic rat model ( 57 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In line with our findings, Huang et al. ( 40 ) reported that the use of insulin is an independent risk factor for DPN in patients with type 2 diabetes. On the other hand, metformin possibly attenuated neuropathic pain in a diabetic rat model ( 57 ).…”
Section: Discussionsupporting
confidence: 93%
“…Insulin was shown to possibly augment the mechanical responsiveness to mechanical stimuli and induce excitation in peripheral nerves in an in vitro study (56). In line with our findings, Huang et al (40) reported that the use of insulin is an independent risk factor for DPN in patients with type 2 diabetes. On the other hand, metformin possibly attenuated neuropathic pain in a diabetic rat model (57).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The model comprised eight variables identified as independent predictors of diabetic neuropath including glycemic control (FBG), other comorbidities, alcohol drinking, Hypertension, type of treatment for DM, physical activity, WBC and RBC count. This result is supported by previous studies conducted [ 36 , 41 , 46 , 61 63 ].…”
Section: Discussionsupporting
confidence: 91%
“…The model comprised eight variables identified as independent predictors of diabetic neuropath including glycemic control (FBG), other comorbidities, alcohol drinking, Hypertension, type of treatment for DM, physical activity, WBC and RBC count. This result is supported by previous studies conducted ( 65), ( 66), ( 37), ( 42), (47), (67).…”
Section: Discussionsupporting
confidence: 91%